Code Smells and Refactorings for Elixir - Vegi, Lucas Francisco da Matta; Valente, Marco Tulio (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2025: Anais do XXIV Simpósio Brasileiro de Qualidade de Software, 2025)
Elixir is a modern functional programming language that is steadily gaining popularity in the industry. However, there is still limited research on the internal code quality produced using this language. To address this gap, this Ph.D. thesis explores code smells and refactorings specific to Elixir, taking inspiration from Fowler’s classic catalogs. The first two studies employed a mixed-methods approach to identify and catalog 35 code smells (including 23 new ones and 12 commonly known), validated by 181 developers, as well as 82 refactorings (14 of which are novel), validated by 151 developers. The third study mapped relationships between code smells and corresponding refactorings, proposing practical guidelines for their systematic elimination. These findings had a real impact on the community of developers working with the language, contributing both to the prevention of code smells and to supporting the prioritization of refactorings in Elixir development.